(untitled) (Baghdad Science Journal, 2012)
Free Radical Copolymerization of Styrene/ Methyl Methacrylate were prepared chemically under Nitrogen ,which was investigated, in the present of Benzoyl Peroxide as Initiator at concentration of 2 × 10-3 molar at 70 °C, which was carried out in Benzene as solvent to a certain low conversion . FT-IR spectra were used for determining of the monomer reactivity ratios ,which was obtained by employing the conventional linearization method of Fineman-Ross (F-R) and Kelen-Tüdos (K- T). The experimental results showed the average value for the Styrene r1 / Methyl Methacrylate r2 system, Sty r1 = 0.45 , MMA r2 = 0.38 in the (F–R) Method and r1 = 0.49 , r2 = 0.35 in the (K–T) Method, The Results of this indicated show the random distribution of monomers in the copolymer.Likewise The monomer reactivity ratios were evaluated Mathematically in comparison in the (F–R) Method with the data STY r1 = 0.61 , MMA r2 = 0.47 , and r1 = 0.45 , r2 =0.38 in the (K–T) Method. And were used the values r1 ,r2 for STY / MMA Copolymers in computing integral curves for the instantaneous Copolymer composition throughout the whole range of conversion.